Effects of Mikania glomerata Leaf Extract on Experimental Bothropoides jararaca Envenomation in Wistar Rats - Motta, Yudney Pereira da; Nogueira, Rosa Maria Barilli; Floriano, Rafael Stuani; Laposy, Cecilia Braga; Camplesi, Annelise Carla; Correal, María Lucía; Sakate, Michiko (Acta Scientiae Veterinariae, 2017)
Background: Bothropic envenomation represents the most common ophidic accident worldwide, compared to other snakebites of medical interest. Bothropic venom has proteolytic, vasculotoxic, clotting and/or hemorrhagic actions in animals and humans. Mikania glomerata is a plant found in the Brazilian Atlantic Forest with interesting medical properties that may be useful in ameliorating the effects of ophidic venom, and thus, improving response and outcome. Although Mikania is known to act through inhibition of cytolysins in the venom, there is a lack of consistent research data. The aim of this study was to evaluate the effect of M. glomerata in bothropic envenomation treatment. Materials, Methods & Results: Clinical, hematological, biochemical, and histopathological evaluations were performed following Bothropoides jararaca experimental envenomation in three groups of 18 Wistar rats each. Group VS was inoculated in the pelvic limb via intramuscular injection of bothropic venom and received specific anti-venom serum via intraperitoneal injection. Group VSM was similarly inoculated; it received anti-venom serum and a 10% aqueous extract of the Mikania glomerata plant orally. Group C was the control group and received saline solution alone. Evaluations were performed at 0.5 h (M1), 6 h (M2), and 24 h (M3) after venom inoculation. Animals from both inoculated groups (VS and VSM) showed significant clinical alterations (P < 0.05) manifested as discomfort, uneasiness, pain, and severe edema compared to control animals. Animals from inoculated groups also exhibited statistically significant leukocytosis with neutrophilia, and elevation of blood urea nitrogen and creatine kinase until 6 h after inoculation (P < 0.05 compared to control animals). An acute drop in body temperature was observed 6 h after inoculation (P < 0.05). High levels of creatinine were observed at 6 and 24 h, and plasma protein reduction at almost all evaluation time points (P < 0.05) in both groups compared to that in control. Histopathological evaluation of venom-inoculated animals (groups VS and VSM) showed significant renal hydropic degeneration, acute tubular necrosis, congestion, and hemorrhage (P < 0.05 compared to control). In contrast, animals administered plant extract in addition to anti-venom (group VSM) showed milder muscular fiber regeneration and absence of hemorrhage in the inoculated limb, compared to those that received anti-venom alone (group VS). Overall, there were no statistically significant differences between the inoculated groups (P > 0.05) in terms of edema reduction, pain relief, hematological, biochemical, or histopathological alterations. Discussion: Clinical envenomation symptoms can be explained based on previous reports of bothropic events, where cytolysins such as hyaluronidase, phospholipase A2, and esterases are associated with alterations in cell membrane permeability and release of vasoactive agents. Rhabdomyolysis and muscular necrosis are the main causes of muscular and renal alterations in inoculated groups. M. glomerata extract is known to exert its inhibitory effects on vasoactive and lytic compounds responsible for muscular necrosis. However, some authors have reported only partial effectiveness of Mikania in inactivating bothropic toxins, in contrast with its greater inhibitory action on crotalic venoms. Further studies are necessary for detailed exploration of the properties of Mikania glomerata extract in order to integrate it into supportive measures for snakebite treatments in tropical and subtropical countries.